Conventional and Pattern Scanning Pan-Retinal Photocoagulation Laser in Diabetic Patients’ Visual Field: Visual Field After Two Types of PRP - Hassanpoor, Narges; Ahoor, Mohamadhosein; Latifi, Atena; Niyousha, Mohamadreza (Journal of Lasers in Medical Sciences, 2022)
Introduction: In this study, we aimed to compare visual field defects in two different laser methods, namely conventional pan-retinal photocoagulation (PRP) and pattern scanning PRP, in patients with either proliferative diabetic or very severe non-proliferative diabetic retinopathy. Methods: This study was a randomized, single-blind, prospective clinical trial. Twenty patients with either proliferative or very severe non-proliferative diabetic retinopathy were enrolled in this study. Notably, only those patients with the same severity scores in both eyes were included. One eye underwent the conventional PRP laser and another eye underwent the pattern scanning PRP laser simultaneously. Swedish interactive threshold algorithms (SITA) standard perimetry was performed at baseline and one month after the treatment, and visual field defects were evaluated. Results: The pattern standard deviation (PSD) significantly increased in both the pattern and conventional PRP laser groups after one month. The change in PSD at baseline and after the treatment was not significant between the groups. The mean deviation (MD) level significantly decreased in the conventional group after one month. The change in the MD level at baseline and after the treatment was not significant between the pattern and conventional groups. The change in the mean best corrected visual acuity (BCVA) between the groups was not significant. Conclusion: Changes in visual acuity and visual fields of the patients between the pattern and conventional PRP laser methods showed no significant difference; however, the pattern PRP method caused a smaller reduction in overall sensitivity in the patient’s visual field.